DNA Metabarcoding Using Indexed Primers: Workflow to Characterize Bacteria, Fungi, Plants, and Arthropods from Environmental Samples - Teresa M. Tiedge; Jorden T. Rabasco; Kelly A. Meiklejohn (Diversity)
Environmental DNA from bulk materials can be analyzed to gain an understanding of the bacterial, fungal, plant, and/or arthropod communities present. DNA metabarcoding is widely used to characterize these biological communities, by amplifying “barcode” regions and sequencing these amplicons via next-generation sequencing. The Earth Microbiome Project (EMP) adopted the use of indexed primers, PCR primers containing Illumina® adapter sequences and a unique 12-nucleotide Golay barcode to simplify the identification of bacterial taxa via the 16S barcode. We sought to develop a wet laboratory workflow utilizing indexed primers that could cost-effectively reduce bench time while simultaneously targeting multiple DNA barcode regions to characterize bacterial (16S), fungal (ITS1), plant (ITS2, trnL p6 loop), and arthropod (COI) communities. The EMP primer constructs for 16S were modified to accommodate our DNA barcode regions of interest while also permitting successful demultiplexing following sequencing. A single indexed primer pair was designed for ITS1 and trnL p6 loop, and two primer pairs were developed for ITS2 and COI. To test the workflow, a total of 648 soil and 336 dust samples were processed, with key steps including DNA isolation, total DNA quantification, amplification with indexed primers, library purification and quantification, and Illumina MiSeq sequencing. Based on raw read counts and analysis of positive controls, the trnL p6 loop and ITS2 a primer pairs performed comparably to the originally designed 16S primers. Both COI primers pairs, ITS1 and ITS2 b primers, had lower raw reads compared to the other three primer pairs. The combination of the three plant targets successfully recovered all plant taxa in the positive controls except for Nephrolepis exaltata [Nephrolepidaceae] and the COI primers recovered all arthropod taxa except for the beetle. Notably, none of the taxa in the fungal positive control were recovered using ITS1. For environmental samples, sequencing was successful for all primers except COI c, and primer biases were observed for all three plant primers, in which a small number of families were uniquely amplified for each primer pair. This workflow can be applied to many disciplines that utilize DNA metabarcoding given its customizability and flexibility with Illumina sequencing chemistry.